Bioinformatics 2014
DOI: 10.1201/b16589-15
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of Three Genome-Wide Association Studies on vWF and FVIII Plasma Levels

Abstract: Background: Elevated levels of factor VIII (FVIII) and von Willebrand Factor (vWF) are well-established risk factors for cardiovascular diseases, in particular venous thrombosis. Although high, the heritability of these traits is poorly explained by the genetic factors known so far. The aim of this work was to identify novel single nucleotide polymorphisms (SNPs) that could influence the variability of these traits. Methods: Three independent genome-wide association studies for vWF plasma levels and FVIII acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…STXBP5 also promoted platelet secretion and thrombosis in mice. Thus, our present data provide strong functional evidence for the regulatory role on circulating vWF and thrombosis by a candidate gene previously identified by GWAS (45)(46)(47)(48)70).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…STXBP5 also promoted platelet secretion and thrombosis in mice. Thus, our present data provide strong functional evidence for the regulatory role on circulating vWF and thrombosis by a candidate gene previously identified by GWAS (45)(46)(47)(48)70).…”
Section: Discussionmentioning
confidence: 62%
“…Recently, genome-wide association studies (GWAS) identified novel genetic variants that are associated with altered plasma vWF levels in humans (45)(46)(47). These genetic loci might indicate novel genes whose products regulate endothelial exocytosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be predicted from GWAS analysis (14)(15)(16)(17)(18)(19), plasma vWF levels were increased in these mice, although plasma IgG was unaffected, as indicated by light chain levels (Supplemental Figure 1). Platelet extracts from Stxbp5 KO and littermate WT mice were prepared Figure 3.…”
Section: Stxbp5 Is Important For Platelet Secretionmentioning
confidence: 72%
“…Deletions in the Stxbp5 gene are linked to autism (36). GWAS show genetic variations in Stxbp5 are linked with increased plasma levels of vWF (14)(15)(16)(17)(18)(19), alterations in tissue plasminogen activator (tPA) levels (20), venous thrombosis (16), and arterial thrombosis (19). Specifically, 1 SNP that produces a nonsynonymous mutation (N436S) was associated with increased bleeding (18).…”
Section: Introductionmentioning
confidence: 99%